Preparation and characterization of Konjac glucomannan and pullulan composite films for strawberry preservation. (1st September 2020) - Yan, Yansu; Duan, Songqi; Zhang, Huilan; Liu, Yuntao; Li, Cheng; Hu, Bin; Liu, Aiping; Wu, Dingtao; He, Jialiang; Wu, Wenjuan
Graphical abstract: Highlights: Konjac glucomannan and pullulan showed good compatibility in the film matrix. The properties of blend films were enhanced due to intermolecular interaction. The KGM/pullulan films preserved strawberries well on different temperatures. The blend films offered a potential alternative to synthetic materials. Abstract: The present study aims to develop the new composite films by blending Konjac glucomannan (KGM) and pullulan with different ratios and concentrations. The structural, physical, barrier properties and morphology of the films were investigated and the practical use on strawberry preservation at 4 ± 1 °C, 85 %±5% relative humidity (RH) and 25 ± 1 °C, 55 %±5% RH was evaluated. Fourier transform infrared and scanning electron microscopy indicated the well-dispersion of film matrix was due to the good compatibility of the components. The mechanical and barrier properties of blend films were markedly enhanced although the light transmittance of which were decreased slightly. It was a further proof that 1% (w/v) KGM/pullulan (with the mass ratio of 2:1) blend film could decrease the weight loss significantly and maintain the titratable acidity, soluble solids and skin color on the strawberry preservation, thus improving the qualities of strawberries during storage time and offering a potential alternative to synthetic materials.